Efeito inibitório do colostro humano sobre biofilme de Escherichia coli - Freire, Suellen Alves (2014)
There are numerous epidemiological evidence indicating protective effect of human milk against a number of microorganisms with which the baby will come into contact in postnatal life, particularly of the respiratory and intestinal tract. Among its various components, IgA is a major immunoglobulin and is present in large quantities in colostrum. In Brazil, Escherichia coli, gram-negative bacillus, has been identified as the most frequently isolated agent in hospitalized children, and often were not breastfed, affecting episodes of severe diarrhea. One of its major virulence factor is the formation of biofilm, which protects against the action of biocides and toxic products. The research aimed to study the in vitro effect of pure and diluted human colostrum and two purified protein fractions (IgA1 and other proteins colostrum) on formation and formed E. coli biofilm. Biomass was measured by staining with crystal violet (CV) 0.4% and viability of the biofilm by colony count on agar plates. In addition, brightfield optical microscopy was used to stain the slides with Congo Red - Carbol-Fuchsin and confocal scanning microscopy using the reagent LIVE/DEAD BacLight ®. There was a dose dependent inhibitory effect on biofilm formation by biomass assay by CV (p <0.001). This data correlated with results of test viability of the biofilm by colony count that also showed a reduction in the number of viable cells (p <0.01). These results were confirmed by microscopy, where the lower dilutions of colostrum and fractions had also an inhibitory effect, showing the formation of clumps similar to the agglutination, with emphasis on the action of IgA1. Data obtained by confocal scanning microscopy showed a decrease in total biofilm area and a significant increase in dead bacteria. With regard to formed biofilm, the data also showed reduced biomass dose-dependent manner, and decrease bacterial viability. Therefore, colostrum serum and their purified fractions have inhibitory effect, decreasing biofilm formation and formed E. coli.